2021
DOI: 10.1111/psyp.13893
|View full text |Cite
|
Sign up to set email alerts
|

Alpha frontal asymmetry underlies individual differences in reactivity to acute psychosocial stress in males

Abstract: People vary in their responses to stress. The present study aimed to investigate whether and how alpha frontal asymmetry (AFA) measured in the resting state underlies the individual differences in psychological responses to acute psychosocial stress (e.g., increases in heart rate and cortisol) induced by the Trier social stress test.Forty-three healthy male adults were enrolled in this study. The results showed that the AFA score negatively predicted both heart rate and cortisol responses, that is relatively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…To reconcile this outcome, we might consider the individual difference in resting state alpha power. Several studies have shown that alpha power asymmetry in the frontal cortex is associated with cognitive control or stress management (Ambrosini and Vallesi 2016;Ma et al 2021). That is, the inherent difference in a participant's alpha power can affect the cybersickness-originated brain activity, and it is critical to clarify the source of alpha power changes.…”
Section: Discussionmentioning
confidence: 99%
“…To reconcile this outcome, we might consider the individual difference in resting state alpha power. Several studies have shown that alpha power asymmetry in the frontal cortex is associated with cognitive control or stress management (Ambrosini and Vallesi 2016;Ma et al 2021). That is, the inherent difference in a participant's alpha power can affect the cybersickness-originated brain activity, and it is critical to clarify the source of alpha power changes.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this finding is rooted in the dominant influence of the characteristics of the eustress group on the overall stress group. Since it is generally acknowledged that the ability of performing tasks follows the inverted U-shaped Yerkes–Dodson model, the abilities of performing tasks under a positive stress condition (eustress) can be more enhanced than that under extreme conditions (negative stress called distress) [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. This explicitly means that the members of the eustress group work faster and more efficiently than those of the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The laterality index for stress (LIS) is mainly used to calculate an asymmetry coefficient in left/right brain patterns between stressed people and unstressed people [ 28 ]. Most studies have shown dominant brain activity in the right hemisphere of people stressed by mental stress tasks [ 29 , 30 , 31 ]. Here, the right hemisphere plays an important role in the diagnosis of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Participants indicate the frequency of their experiences of the 20 SDS items during the last two weeks as “None or a little of the time” (score = 1), “Some of the time” (2), “Good part of the time” (3), or “Most or all of the time” (4). The SDS produces total scores from 20 to 80 [ 45 , 47 ], with 40 or above indicative of “clinically significant depression” [ 47 ] (p. 335). The SDS has split-half reliability of .81, [ 45 ], .79 [ 48 ] and .94 [ 49 ], with an internal consistency (alpha) of .88 for depressed patients and .93 for non-depressed patients [ 50 ].…”
Section: Methodsmentioning
confidence: 99%